Analisis Kemenangan Calon Independen Pasangan Abdul Hafidz-Bayu Andriyanto Dalam Pilkada Kabupaten Rembang Tahun 2015 - Widiptya, Gholal Pusthika; Utomo, Susilo (Journal of Politic and Government Studies, 2017)
Indonesia as a democratic country puts the supreme power on people's hands by holding elections to choose candidates for the leader. Of 269 simultaneous elections held in 2015, one of the interesting local elections are elections Rembang. Rembang’s local leader election be attractive because candidates who advanced through independent pathways emerged as the winner defeating another pair of candidates backed by the major parties.The method used is a qualitative approach to data collection techniques are in-depth interviews. Informants in this study are H. Abdul Hafidz as a candidate who won the election Rembang 2015, Pair candidates Abdul Hafidz-Bayu Andriyanto’s team, Pair candidates Hamzah Fatoni-Ridwan’s team, Pair candidates Sunarto-Kuntum Khairu Basa’s team, Regional general election commitee, Election supervisory committee.These results indicate that there are four factors that influence the election of candidates Abdul Hafiz-Bayu Andriyanto advanced through individual lines can emerge as winners beat another candidates pair who supported the major parties. First, Abdul Hafidz figure already strong in Rembang, because of its track record as a member of third period parliament and incumbent. Second, the strength of the political machine possessed, as though advancing through independent channels, but there are three political parties PPP, Nasdem, and PAN are supporting a successful team despite not officially registered at the Commission as a party supporter. Third, the strategy adopted by successful teams effective in reaching people both constituents and non-participants, provide vision and mission as well as a good program, and in addition the pair advanced through independent channels are also benefited by being able to campaign at the time of collecting evidence of support as required by the Commission before another pair of candidates can campaign. Fourth, the economic capital of the pair is superior to the other candidate pairs, economic capital is then used to make money politics given the characteristics of voters in Rembang pragmatic.Keywords : Local Leaders Election, Independent Candidates, the winning of Independent Candidates